KUALITAS AUDITOR EKSTERN DALAM MEMBATASI KESEMPATAN MANAJEMEN UNTUK MELAKUKAN MANAJEMEN LABA - Prihat Assih (Jurnal Keuangan dan Perbankan, 2009)
Earnings management practice related to a variety incentives to maximize fi rms value orto increase manager welfare. Many researchers focused on 3 main incentives for earnings managementpractice, as explained in positive accounting theory, that were incentive to decrease cost ofdebt covenant default, maximize bonus and reduce political cost (Watts Zimmerman, 1986). However,the earnings management would exist if management had incentive and opportunity to do so(Trueman Titman, 1988; Christensen, et al., 1999). The objectives of this research was to investigateexternal auditor quality as factor to constraining earnings management by managers. Analysis wasbased on 111 publicly manufacturing fi rms in Indonesian Stock Exchange period 2005 up to 2008.The result showed that the high level of fi rms debt motivated manager to practice more earningsmanagement. However, the level of earnings management was lower when the quality of auditorexternal work was higher. The results of these research contributed to accounting literature developmentespecially in corporate governance. Qualifi ed auditor, one of monitoring aspects, had functionas good corporate governance mechanism for reducing management practice to manage earningswhich would be costly for fi nancial statement users.